Leadership Style And Its Impact On Nurses Level Of Work Motivation - Dewi Reto Puspitosari; Titik Juwariyah; Agus Priyanto (Jurnal Pendidikan dan Konseling (JPDK), 2020)
Work motivation is the spirit that can drive nurses to perform their activities or duties in order to achieve organizational goals, and motivate every nurse to have not only personal needs but also the advancement of nursing services in an institution. The purpose of this study is to analyze the leadership style and work motivation of nurses at the Pesantren II Kediri Community Health Center. This research is quantitative in nature with a descriptive correlational research design. The population in this study consists of all employees of the Pesantren II Kediri Community Health Center, totaling approximately 21 individuals. Primary data collection was conducted through questionnaires. The results of the study indicate that the leadership style applied by the head of the department includes democratic, participative, authoritarian, and laissez-faire styles. The performance of nurses, including the stages of assessment, diagnosis, intervention, implementation, and evaluation, is categorized as good. There is an influence of participative, authoritarian, and laissez-faire leadership styles on the performance of implementing nurses. The conclusion of this study is the presence of an influence of leadership style on the performance of implementing nurses at the Pesantren II Kediri Community Health Center. The leadership should apply an appropriate leadership style tailored to the working conditions and the needs of implementing nurses in order to enhance the performance of nursing care services in the healthcare facility.